(untitled) (Analele Universității din București - Istorie, 2024)
The whole life of Ebbon, church hierarch, missionary, man of letters and 9th century politician, points without a doubt to a character who was never satisfied with what he had, what he knew or what he achieved. We intend to show to what extent this personal insatisfaction with his lot played a role în finding new ways of visual expression which marked the transition from antique models towards a new, middle ages esthetics.